Indo-European loanwords and exchange in Bronze Age Central and East Asia: Six new perspectives on prehistoric exchange in the Eastern Steppe Zone. (22nd April 2022) - Bjørn, Rasmus G.
Abstract: Abstract: Loanword analysis is a unique contribution of historical linguistics to our understanding of prehistoric cultural interfaces. As language reflects the lives of its speakers, the substantiation of loanwords draws on the composite evidence from linguistic as well as auxiliary data from archaeology and genetics through triangulation. The Bronze Age of Central Asia is in principle linguistically mute, but a host of recent independent observations that tie languages, cultures and genetics together in various ways invites a comprehensive reassessment of six highly diagnostic loanwords ('seven', 'name/fame', 'sister-in-law', 'honey', 'metal' and 'horse') that are associated with the Bronze Age. Moreover, they are shared between Indo-European, Uralic, Turkic and sometimes Old Chinese. The successful identification of the interfaces for these loanwords can help settle longstanding debates on languages, migrations and the items themselves. Each item is analysed using the comparative method with reference to the archaeological record to assess the plausibility of a transfer. I argue that the six items can be dated to have entered Central and East Asian languages from immigrant Indo-European languages spoken in the Afanasievo and Andronovo cultures, including a novel source for the 'horse' in Old Chinese.